Putative mechanisms responsible for the antihyperglycemic action of lactobacillus paracasei hii01 in experimental type 2 diabetic rats - Parichart Toejing (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Despite the updated knowledge of the impact of gut dysbiosis on diabetes, investigations into the beneficial effects of individual bacteria are still required. This study evaluates the antihyperglycemic efficacy of Lactobacillus paracasei HII01 and its possible mechanisms in diabetic rats. Diabetic rats were assigned to receive vehicle, L. paracasei HII01 (108 CFU/day), metformin 30 (mg/kg) or a combination of L. paracasei HII01 and metformin. Normal rats given vehicle and L. paracasei HII01 were included. Metabolic parameters, including in vitro hemi-diaphragm glucose uptake, skeletal insulin-signaling proteins, plasma lipopolysaccharide (LPS), gut permeability, composition of gut microbiota and its metabolites, as well as short-chain fatty acids (SCFAs), were assessed after 12 weeks of experiment. The results clearly demonstrated that L. paracasei HII01 improved glycemic parameters, glucose uptake, insulin-signaling proteins including pAktSer473, glucose transporter 4 (GLUT4) and phosphorylation of AMP-activated protein kinase (pAMPKThr172), tumor necrosis factor (TNF-α) and nuclear factor-κB (NF-kB) in diabetic rats. Modulation of gut microbiota was found together with improvement in leaky gut, endotoxemia and SCFAs in diabetic rats administered L. paracasei HII01. In conclusion, L. paracasei HII01 alleviated hyperglycemia in diabetic rats primarily by modulating gut microbiota along with lessening leaky gut, leading to improvement in endotoxemia and inflammation-disturbed insulin signaling, which was mediated partly by PI3K/Akt signaling and AMPK activation.